(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
A computational investigation of Couette flow of heat generating/absorbing fluid in a channel due to nonlinear thermal radiation, temperature dependent viscosity and temperature dependent thermal conduction is considered in this paper. The channel in which the fluid flow is assumed to be formed by two parallel infinite vertical plates in which one of the plates is assumed to move with a constant velocity in the direction of fluid flow while the other is stationary. A uniform radiative heat flux applied through the moving porous channel and this penetrate into the fluid. The fluid is considered to be a heat generating/absorbing one and that both its viscosity and thermal conduction depend on temperature variation. Under these assumptions, the mathematical equations representing this flow are given and are solved using a semi-analytical method of solution and computer simulation. To witness the insight of the flow phenomenon; graphs of velocity and temperature fields are displayed for the pertinent parameters of interest with discussion.